Sales location among semi-subsistence cassava farmers in Benin: A heteroskedastic double selection model - Takeshima, Hiroyuki; Winter-Nelson, Alex (Wiley, 2012)
In much of rural Africa, high transaction costs limit farmers’ market participation and thus their potential for income growth. Transaction costs can affect not only whether a farmer sells product but also whether sales occur at the farm gate or at a market. If production behavior is related to a chosen sales location, then analysis of interventions can be improved by explicit consideration of the decision of where to sell. This article develops a double‐selection model that explains consumption and production decisions by semi‐subsistence farmers who first decide whether to be a seller and then whether to sell at the farm gate or at an off‐farm location before deciding on production and consumption. The study tests the validity of this dual‐criteria model against a single‐criterion model in which a grower first decides to be a seller and then decides production, consumption, and sales location simultaneously. The results suggest that the dual‐criteria model provides more information than the single‐criterion model using a sample of cassava producer in Benin.